THE CONTEMPORARY AUTOMATIC GEARBOXES - REVIEW OF THE CURRENT STATE AND INTERPRETATION OF ADVANTAGES AND DISADVANTAGES OF THEIR USE WITH RESPECT TO VEHICLE PERFORMANCE AND TRAFFIC SAFETY - Stanojević, Darko D; Stevanović, Igor; Spasojević, Vladimir; Nedić, Aleksandar (Journal of Applied Engineering Science, 2013)
The aim of this paper is to present the current state of development level of contemporary automatic gearboxes in the automotive industry, their level of presence, as well as to bring the concept of a possible positive impact of their use on road safety as a solution designed with a high percentage of electronic components and cybernetics. The first section provides an overview of the types of automatic gearboxes in recent time and a short  description of their function principles. The second section provides interpretation of possible positive efects of their using in automotive industry with respect to vehicle performance and traffic safety.
Keywords: Automotive Industry; Vehicle performance; Traffic safety; Contemporary automatic gearboxes